Relationship Between Digital Health Literacy and Hypertension Preventive Behavior among Adolescents in Urban Areas - Hendra Dwi Kurniawan; Safaruddin Safaruddin; Rizki Aqsyari (Pakis Journal Institute, 2026)
Hypertension in adolescents is an emerging public health concern because it can increase the risk of cardiovascular complications later in life. The advancement of digital technologies has made digital health literacy an important factor in shaping hypertension prevention behaviors. This study aimed to analyze the association between digital health literacy and hypertension prevention behaviors among adolescents in urban areas. A cross-sectional observational analytic design was employed, with a sample of 225 adolescents selected using purposive sampling. Data were collected using questionnaires on digital health literacy and hypertension prevention behaviors and analyzed using the Chi-square test. The results showed that most respondents had good digital health literacy and demonstrated appropriate hypertension prevention behaviors. Bivariate analysis indicated a significant association between digital health literacy and hypertension prevention behaviors (p < 0.001; OR = 3.225; 95% CI: 1.713–6.071). Adolescents with good digital health literacy were more likely to engage in hypertension prevention behaviors. Enhancing digital health literacy is a crucial strategy for promotive and preventive efforts targeting hypertension among adolescents in urban settings.